Pakistan’s Approach to Climate Change Diplomacy: An Analysis of SDG13 - Mehwish; Sabeen Azam; Dr. Akhlaque Hussain Larik; Zuberia Sadiq; Sadaf Jan Siddiqui; Umaima Iqbal (Dialogue Social Science Review (DSSR), 2025)
This research critically examines Pakistan’s approach to climate change diplomacy, focusing on the state's policies and strategies aimed at achieving SDG 13 targets. A qualitative methodology is being applied in this study to integrate policy analysis, secondary literature, and primary data that is collected through secondary resources to address the primary research questions. The results shown are that there are more challenges, such as constrained financial resources, underdeveloped infrastructures, and a population highly susceptible to extreme weather events. Despite these obstacles, Pakistan’s institutional frameworks and policies reflect aspirations to address climate change at local, national, and international levels. However, systemic issues such as governance deficiencies, inadequate international support, and weak policy implementation continue to impede progress. Pakistan’s position as one of the most climate-vulnerable nations, despite its minimal contribution to global emissions, necessitates tailored approaches distinct from those applied to other nations. The research highlights improvement, better compliance with climate policies, and more financing for adaptation and mitigation activities. Key recommendations are the development of consistent climate diplomacy strategies, mainstreaming climate change into national policies, and addressing governance gaps to support effective policy execution. All this is needed for Pakistan to achieve its climate objectives and meaningfully contribute to the global fight against climate change.